Measuring performance of linear assets considering their spatial extension. Issue 3 (5th August 2014) - Uday Kumar, Associate Professor Aditya Parida and Associate Professor Ramin Karim, Professor; Stenström, Christer; Parida, Aditya
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate how performance of linear assets can be analysed and displayed, considering both the technical asset and the user context, to simplify cognitive tasks of planning and decision making. Design/methodology/approach – Linear, or continuous assets, such as roads, railways, electrical grids and pipelines, are large, geographically spread out technical systems. Linear assets are comprised of system, subsystem and component levels. Thus, asset managers are involved with each level of the linear asset; asset management has strategic, tactical and operational levels. A methodology is developed to link together the technical and organisational levels and to measure asset performance considering their spatial extension. Geographical location and time are used as independent variables. Findings – For performance measurement of linear assets, it is found that the spatial extension is an equally generic dimension as time is for technical assets in general. Furthermore, as linear assets actually are combinations of linear and point assets; separate analysis of these assets is a prerequisite. Asset performance has been studied in a case study in terms failures and cost; the results indicate that the methodology visualise poor, as well as good, performance in an easy to interpret manner. Besides, the results indicate that other parameters related to dependability can be presented in a similar way. Practical implications – This study highlights the importance of including the spatial or geographical extension of linear assets in infrastructure managers' performance measurement. It is believed that the methodology can make planning and decision making more effective by pointing out improvement areas in technical assets, in a way that is appealing to both technicians and managers. Social implications – As infrastructure managers are improving their analysis and visualisation of performance, the public's interest of following the information increases, which in turn contributes to the connection between infrastructure managers and the public. Originality/value – The presented methodology and case study analysed performance in function of both the technical and organisational levels, including the spatial component. It is believed that the methodology for analysing and visualising performance of linear assets is distinctive.